Revealing the Legal Protection of Patients Social Security Administration Agency of Health in Sanglah and Balimed Hospitals Denpasar - RA Tuty Kuswardhani; I Nyoman Budiana (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2020)
Social Security Administration Agency of Health has a National National Health Insurance formulary, but in reality patients do not get drugs according to the National Health Insurance National Formulary. Therefore, the aims of this study are to determine the legal protection of patients of the Social Security Administration Agency of Health for the elderly in curative therapy in hospitals according to the national formulary of National Health Insurance at Sanglah Hospital and Balimed Hospital, and to know the responsibilities undertaken by the Social Security Administration Agency of Health in fulfilling its obligations for patients the Agency for the Implementation of the Social Health Insurance of the elderly in curative therapy in accordance with the national formulary of the National Health Insurance. This study uses a participatory observational (empirical-observational) empirical legal research method. Sampling with purposive sampling and data collection techniques using triangulation techniques. In principle, legal protection must refer to legal certainty, fairness and benefits for the population participating in the Social Security Administration Agency of Health for the elderly so that it is not impressed that Balimed Hospital and Sanglah General Hospital and the Social Security Administration Agency of Health make a service to consumers who are not good. The legal responsibility that should be obtained by the participants of the Social Security Administration Agency of Health for the elderly in Balimed Hospital and Sanglah Hospital Denpasar which is currently not maximally received by patients participating in the Social Security Administration Agency of Health for the elderly at Balimed Hospital and Sanglah Hospital.